Estilos de aprendizaje y resolución de problemas de cantidad en estudiantes de la Institución Educativa República del Perú N° 601014 Mariscal Ramón Castilla 2022 - Gonzales Pacaya de Tapullima, Flor del Carmen (2025)
The general objective was to establish the relationship between learning styles (active, reflective, theoretical, and pragmatic) and the resolution of quantity problems among third-year secondary students at the Institución Educativa República del Perú 601014 in Caballo Cocha in 2022. Research type: descriptive correlational, with a quantitative approach and a non-experimental field design, cross-sectional. Population and sample: 27 students. Instruments: The CHAEA (Honey-Alonso) questionnaire consisting of 80 questions on learning styles and an 8-question test on the resolution of quantity problems were administered. Statistical analysis: Descriptive – 81% of the students were classified as having an average learning style, with 52% of the students reaching the “process” level, while only 4% achieved the “destacado” level. Inferential – Spearman’s Rho correlation showed a moderate positive relationship (ρ = 0,599; p < 0,001) between the variables. At the dimensional level, the active learning style presented the highest correlation (ρ = 0,705), followed by pragmatic (ρ = 0,564), theoretical (ρ = 0,494), and reflective (ρ = 0,337), all with a significance level of p < 0,001. Conclusions: It was established that there is a significant relationship between learning styles and the resolution of quantity problems, validating none of the hypotheses. In this sense, the active learning style had the greatest impact, while the relationship for the reflective learning style was the lowest of all in terms of resolving quantity problems.